PENYERANGAN TERHADAP HORS DE COMBAT DALAM KONFLIK BERSENJATA BERDASARKAN PRINSIP PEMBEDAAN: Attacks Againts Hors De Combat in Armed Conflict Based on The Distinction Principle - Salsabilah, Nahdia; Wibowo, Aji (Faculty of Law, Universitas Trisakti, 2025)
This research analyzes and discusses hors de combat as a subject in International Humanitarian Law, focusing on implementing the principle of distinction in armed conflict. The discussion arises from frequent misunderstandings about the subjects of International Humanitarian Law, which juxtaposes combatants with non-combatants. Article 10 of Additional Protocol I of 1977 states that International Humanitarian Law respects and protects all wounded, sick, and shipwrecked persons. Therefore, this paper will discuss the position of combatants who cannot participate in hostilities due to the reasons mentioned in the article and how International Humanitarian Law protects them. This research will discussed the issue in relation to the problems that occured during the conflict between Palestine and Israel in 2024.